Local seismic systems for study of the effect of seismic waves on rock mass and ground support in Swedish underground mines (Zinkgruvan, Garpenberg, Kiruna) - Dineva, Savka; Mihaylov, Dimitar; Hansen-Haug, Jouni; Nyström, Anders; Woldemedhin, Biruk (Luleå tekniska universitet, Geoteknologi, 2016)
Three local seismic systems were installed by August 2015 in deep underground mines in Sweden – Zinkgruvan Mine (Lundin Mining AB), Garpenberg Mine (Boliden AB), and Kiirunavaara Mine (LKAB) as part of a project for developing new methods for Evaluating the Rock Support Performance (ERSP, Vinnova). The areas were chosen within the most probable volumes where large rockbursts can be expected. The local systems were installed at mine levels between 730 and 1150 m in different mines. The horizontal extend of each instrumented areas is between 70 and 100 m. The seismic system in each mine is a combination of uni-axial and three-axial 4.5 Hz geophones installed on the surface, in shallow (~0.5 m) and deeper (6-9 m) boreholes in profiles across drifts. These profiles are in close proximity to profiles with extensometers, instrumented bolts, and observation holes. The seismic systems are manufactured and installed by the Institute of Mine Seismology (IMS). The aim of the seismic systems is to record the seismic events that occur in the vicinity of the instrumented areas and provide valuable data about the variability of seismic waveforms around the underground openings and changes when seismic waves approach them. Data is used to study: 1) the attenuation/decrease of the maximum ground velocity (PPV) with the distance, especially at small distances; 2) site effects, including maximum amplitudes, predominant frequency, and duration of the seismic signals, 3) the attenuation/amplification of the seismic waves approaching the underground opening. The final aim is to obtain new information that can be used for improved requirements for the rock support design in rockburst prone areas.The installation of the seismic systems started in May 2015 (Zinkgruvan Mine) and was completed by August 2015. They run mostly in triggered mode with initial automatic arrival time picking and source parameter calculation and subsequent manual processing of seismic event of interest. More than 200,000 seismic events with magnitude from -4.5 ...